Sticky traps for Aedes aegypti surveillance and targeted vector control in Sincelejo, Colombia. - Sermeño-Correa, Carlos; Bedoya-Polo, Alexander; Camacho, Erwin; Bejarano-Martínez, Eduar (Biomédica: Revista del Instituto Nacional de Salud, 2025)
Introduction. Entomological surveillance of adult Aedes aegypti mosquitoes provides better risk indicators than in immature stages. Objective. To determine the usefulness of MosquiTRAP™ traps for Ae. aegypti surveillance, targeted vector control, and the design of dengue prevention measures in Sincelejo, Colombia. Materials and methods. Forty-nine MosquiTRAP™ traps were deployed over six months to capture gravid Ae. aegypti females in two neighborhoods with historical reports of dengue cases. Entomological indices were calculated to monitor mosquito population dynamics, and the infection frequency of the captured mosquitoes with dengue, zika, and chikungunya virus were assessed. The rates of trap approval and adherence were evaluated, and risk maps were developed based on mosquito abundance. These maps facilitated the identification of specific areas for targeted vector control interventions. Results. A total of 1,475 mosquitoes were captured, of which 99.1% were identified as A. aegypti. The trap positivity index ranged from 85.7 to 42.9% per inspection, with a mean female Aedes index of two to three mosquitoes per house. Evidence of Ae. aegypti infestation was observed in both neighborhoods, although specific hotspots of high mosquito abundance were identified. No viral infection was detected in the captured mosquitoes. Conclusions. MosquiTRAP™ traps are useful for Ae. aegypti surveillance as a potential tool to guide vector control and prevention measures for diseases transmitted by this mosquito species.